Master the art of speed painting : digital painting techniques - Cording, Debbie; Morse, Simon, 1984-; 3dtotal Publishing (Worcester, United Kingdom : 3dtotal Publishing, 2016)
For matte painters and concept artists working in the movie, videogame, and TV industry, it can often be important to be able to quickly and efficiently create artwork, for storyboarding and storytelling purposes. Master the Art of Speed Painting: Digital Painting Techniques aims to be the go-to book for artists training to enter the industry, and for established artists looking to brush up on their knowledge of speed painting. Featuring helpful time-saving tips and techniques from established industry artists, such as how to create and use custom brushes, and how to implement an impressionistic style, there's plenty to offer to help the artist master their craft. In addition, there are time-specific guides for painting in 10-, 30-, 60- or 120-minute periods, all to enable the artist to tailor their abilities to suit any situation that might arise in the high-pressure, time-sensitive creative industry. Become a speed-painting master in no time! Master the Art of Speed Painting: Digital Painting Techniques also aims to fill a void within the digital art book market, as no directly comparative title currently exists. In today's fast-moving world, speed is often of the essence, and this book will become an essential guide for students and established artists alike.
Introduction -- Techniques Custom brushes Photobashing -- Gallery -- 2-hour painting Sci-fi: late expedition Fantasy: an unexpected place Horror: ward away -- Real world: historical landscape Horror: doom head Sci-fi: old shore Real world: seascape Fantasy: night storm Fantasy: the dome Fantasy: serenity -- 1-hour painting Sci-fi: forgotten explorers Sci-fi: Mars factory Fantasy: face your fears Sci-fi: a modern interior Sci-fi: the future Fantasy: monumental ruin Fantasy: ice world Real world: urban sketching Real world: night scene Fantasy: the waterway -- 30-minute painting Sci-fi: mobile lab Sci-fi: checkpoint on Mars Fantasy: letting it flow Fantasy: flyover -- Film noir: bang: 10 minutes! -- A master class with Thomas Scholes -- Meet the artists.
Includes index.
Keywords: Computer art -- Technique; Painting -- Technique